Mental health among medical professionals during the COVID-19 pandemic in eight European countries: cross-sectional survey study - Hummel, Svenja; Oetjen, Neele; Du, Junfeng; Posenato, Elisabetta; Almeida, Rosa Maria Resende de; Losada, Raquel; Ribeiro, Oscar; Frisardi, Vincenza; Hopper, Louise; Rashid, Asarnusch; Nasser, Habib; König, Alexandra; et al. (Journal of medical internet research, 2021)
Background: The death toll of COVID-19 topped 170,000 in Europe by the end of May 2020. COVID-19 has caused an immense psychological burden on the population, especially among doctors and nurses who are faced with high infection risks and increased workload. - Objective: The aim of this study was to compare the mental health of medical professionals with nonmedical professionals in different European countries during the COVID-19 pandemic. We hypothesized that medical professionals, particularly those exposed to COVID-19 at work, would have higher levels of depression, anxiety, and stress. We also aimed to determine their main stressors and most frequently used coping strategies during the crisis. - Methods: A cross-sectional online survey was conducted during peak COVID-19 months in 8 European countries. The questionnaire included demographic data and inquired whether the participants were exposed to COVID-19 at work or not. Mental health was assessed via the Depression Anxiety Stress Scales32 (23.53)-21 (DASS-21). A 12-item checklist on preferred coping strategies and another 23-item questionnaire on major stressors were completed by medical professionals. - Results: The sample (N=609) consisted of 189 doctors, 165 nurses, and 255 nonmedical professionals. Participants from France and the United Kingdom reported experiencing severe/extremely severe depression, anxiety, and stress more often compared to those from the other countries. Nonmedical professionals had significantly higher scores for depression and anxiety. Among medical professionals, no significant link was reported between direct contact with patients with COVID-19 at work and anxiety, depression, or stress. “Uncertainty about when the epidemic will be under control” caused the most amount of stress for health care professionals while “taking protective measures” was the most frequently used coping strategy among all participants. - Conclusions: COVID-19 poses a major challenge to the mental health of working professionals as a considerable proportion of our participants showed high values for depression, anxiety, and stress. Even though medical professionals exhibited less mental stress than nonmedical professionals, sufficient help should be offered to all occupational groups with an emphasis on effective coping strategies. - [J Med Internet Res 2021;23(1):e24983]